Molecular structure characterization of middle-high rank coal via 13C NMR, XPS, and FTIR spectroscopy - Xiao-ming Ni; Jing-shuo Zhang; Xiao-kai Xu; Bao-yu Wang (China Geology, 2024)
ABSTRACT: Elemental analysis, nuclear magnetic resonance carbon spectroscopy (13C-NMR), X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR) experiments were carried out to determine the existence of aromatic structure, heteroatom structure and fat structure in coal. MS (materials studio) software was used to optimize and construct a 3D molecular structure model of coal. A method for establishing a coal molecular structure model was formed, which was “determination of key structures in coal, construction of planar molecular structure model, and optimization of three-dimensional molecular structure model”. The structural differences were compared and analyzed. The results show that with the increase of coal rank, the dehydrogenation of cycloalkanes in coal is continuously enhanced, and the content of heteroatoms in the aromatic ring decreases. The heteroatoms and branch chains in the coal are reduced, and the structure is more orderly and tight. The stability of the structure is determined by the π-π interaction between the aromatic rings in the nonbonding energy EN. Key Stretching Energy The size of EB determines how tight the structure is. The research results provide a method and reference for the study of the molecular structure of medium and high coal ranks.